2022
DOI: 10.1123/ssj.2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Enactments of Integrated, Disability-Inclusive Sport Policy by Sporting Organizations

Abstract: This article critically analyzed the enactment of disability-inclusive sport policies by provincial sporting organizations in British Columbia. Thirty semistructured interviews with managers representing 13 organizations informed the analysis. Findings highlighted how organizational circumstances prompted managers to enact integration policies in novel ways at the regional level. For instance, nondisabled sporting organizations mediated the adoption of integration policies due to the perceived impact on nondis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…This finding is consistent with other studies which have found coaches do not view promoting diversity or inclusion of athletes with disability as part of their role (Hammond, 2022;Hammond et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies which have found coaches do not view promoting diversity or inclusion of athletes with disability as part of their role (Hammond, 2022;Hammond et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This research corresponds with existing scholarship on disability and sports that centres the experiences of (recreational) athletes in integrative and adaptive sports (Clair, 2011; D’Eloia and Price, 2018; Hammond et al, 2022; Kiuppis, 2018). It builds upon existing scholarship on the experiences of visually impaired athletes that suggest that guided running creates positive feelings and increases physical activity among visually impaired runners (Hall et al, 2022; Jaarsma et al, 2014), and aligns with research on organized runs for visually impaired runners and their guides as part of inclusive strategies (Fullagar et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…We argued that the language of inclusion does not explicitly evoke a commitment to action or to challenge inequalities. Nor does it explicitly challenge power relations and the political landscape of who gets to decide who ‘is to be included’ and whether someone or something is ‘inclusive’ (Hammond et al, 2022; Hassanein, 2015). By doing so, our study offers insight into the lived experience of inclusion which is different than how sports inclusion is typically constructed and framed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel arrangement of the Olympic Games followed a few weeks later by the Paralympic Games is an example of how competitions reproduce segregation whereas the Commonwealth Games that include events for athletes with and without disabilities is one of the few examples of an integrated competition in elite sport (Quinn et al, 2020). While much has been written on integration in sport contexts including exploring attitudes toward disability amongst those directly involved in integrated events (see for example, Misener et al, 2015;Paradis et al, 2017;Quinn et al, 2020), managerial perspectives on integration policies and sport delivery (Kitchin and Howe, 2014;Hammond et al, 2021) and the experiences of para-athletes in integrated organizations (Howe, 2007), little research has considered how the implications of integration shape and constrain athlete wellbeing.…”
Section: Ableist Structures and Psycho-emotional Disablismmentioning
confidence: 99%